Economics of Ar-Rahnu (Islamic pawnbroking): issues and cases in Brunei Darussalam - Kambara, Kentaro (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aims of this paper are to discuss issues on Ar-Rahnu in relation to Islamic jurisprudence and as a financial product in Brunei Darussalam. There are critical issues of Rahn in Islamic jurisprudence. The first issue is the debtor fails to repay his debt at maturity (default) and the second issue is benefiting from pledged property. Furthermore, Ar-Rahnu products in Brunei have strong characteristics as a financial product for SME (small and middle enterprises). Ar-Rahnu products in Brunei also can help entrepreneurs to purchase textile machines, necessary equipment and other crucial materials for their paddy planting and processing business. There are two feature of Ar-Rahnu products, first feature is the discussion on property. In the case of default, the creditor pays over the surplus to a borrower after the creditor has auctioned the borrower’s collateral. This proves that there is a difference between Ar-Rahnu products and conventional pawnbroking with regard to the concept of property. Therefore, it is important to make further research on this subject to enhance Islamic financing. The second feature of Ar-Rahnu products is it is a financial product for SME, but it can also be used for lower-income groups, especially for assisting with living expenses. This shows the diversity of Ar-Rahnu products. Therefore, researches of Ar-Rahnu products have more importance in the future in terms of Islamic jurisprudence and financial products.